Fragmentação socioespacial em cidades médias paulistas - Dal Pozzo, Clayton Ferreira [UNESP] (2015)
Among the beginning twentieth century until the mid-1970s, the structure of middle-size cities and metropolitan cities of São Paulo State was based, preponderantly, on the center-periphery differentiation and imposed segregation, which helped to strengthen the trend occupying the periphery for the poorest. With the implementation and occupation of segregated spaces and central areas on the urban peripheries, showed up the first dynamic involving the restructuring of cities, such as: - territorial expansions that tended to diversify the contents of the periphery, however, accompanied by disruptions with territorial continuity; new spatial practices that segment the consumption of the city; changes in the context of socio-spatial relations among citizens. Such dynamics explain socio-spatial fragmentation characteristic that are not more exclusive of the metropolitan cities, because, this also started to evidence in middle-size cities of São Paulo State. The segmentation tendency between the different social groups began to consolidate not only considering the residential scale, but also tended to be extended to encompass the consumption of urban space. With that, the fragmentation socioespacial intensifies the socio-spatial inequalities and it depreciates the territorial unit of the city. The research carried out in Presidente Prudente and Ribeirão Preto of São Paulo State, details the development of that process